2014
DOI: 10.1016/j.gene.2013.11.065
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the 78 kD glucose-regulated protein is induced by endoplasmic reticulum stress in the development of hepatopulmonary syndrome

Abstract: Objective This study is to explore the role of 78 kD glucose-regulated protein (GRP78) in development of hepatopulmonary syndrome (HPS) in rats. Methods The rat model of liver cirrhosis and HPS were induced with multiple pathogenic factors. Hematoxylin and eosin (H & E) staining was performed to detect the pathological changes of the lung and liver tissues. The levels of alanine transferase (ALT), endotoxin, and tumor necrosis factor-α (TNF-α) in plasma and TNF-α and malondialdehyde (MDA) in lung tissues wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Previous studies demonstrated that the waterfall effect resulting from inflammatory cytokines induced by endotoxin played a pivotal role in the liver injury of NAFLD2930. Endotoxin could also directly damage hepatocytes and activate kupffer cells to produce inflammatory cytokines followed by the waterfall effect and release of oxygen radicals, which may cause liver damage.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that the waterfall effect resulting from inflammatory cytokines induced by endotoxin played a pivotal role in the liver injury of NAFLD2930. Endotoxin could also directly damage hepatocytes and activate kupffer cells to produce inflammatory cytokines followed by the waterfall effect and release of oxygen radicals, which may cause liver damage.…”
Section: Discussionmentioning
confidence: 99%
“…We also measured the glucose-regulated protein GRP78/Bip mRNA expression, which is a marker of ER stress. 42 The chaperone proteins, such as GRP78/BiP, GRP94, are major regulators of all three pathways. 43 The results further validated that clofoctol and sorafenib could lead to synergistic PC-3 cell death via induction of ER stress by activating UPR pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Misfolding of proteins can be caused by endogenous factors such as genetic mutations, as well as exogenous factors such as I/R-initiated abnormal oxidative status and disrupted calcium homeostasis [27,28]. Glucose-regulated protein 78 (Grp78) is an important ER molecular chaperone regulating protein folding, facilitating, translocation, and secretion in the ER [29]. Under homeostatic conditions, Grp78 is bound to 3 ER transmembrane proteins that act as signal transducers, activating transcription factor 6 (ATF6), inositol-requiring enzyme 1 (IRE1), and protein kinase-like ER kinase (PERK) [30].…”
Section: Discussionmentioning
confidence: 99%